2014
DOI: 10.1002/jmr.2342
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation studies for DNA sequence recognition by reactive metabolites of anticancer compounds

Abstract: The discovery of novel anticancer molecules 5F-203 (NSC703786) and 5-aminoflavone (5-AMF, NSC686288) has addressed the issues of toxicity and reduced efficacy by targeting over expressed Cytochrome P450 1A1 (CYP1A1) in cancer cells. CYP1A1 metabolizes these compounds into their reactive metabolites, which are proven to mediate their anticancer effect through DNA adduct formation. However, the drug metabolite-DNA binding has not been explored so far. Hence, understanding the binding characteristics and molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…The metabolic profile of AF demonstrated that CYP1A1 and sulfotransferase 1A1 (SULT1A1) metabolize the two amino groups successively, initially to toxic hydroxylamines, then to active nitrenium ions (Scheme ) . Nitrenium ion species bind with DNA, forming DNA adducts; leading to cell death . The di‐nitrenium ion 26 inhibits DNA synthesis via inducement of S‐phase arrest and replication‐dependent histone H2AX phosphorylation; resulting in DNA double‐strand breaks and ultimately cytotoxicity .…”
Section: Exogenous Ligandsmentioning
confidence: 99%
“…The metabolic profile of AF demonstrated that CYP1A1 and sulfotransferase 1A1 (SULT1A1) metabolize the two amino groups successively, initially to toxic hydroxylamines, then to active nitrenium ions (Scheme ) . Nitrenium ion species bind with DNA, forming DNA adducts; leading to cell death . The di‐nitrenium ion 26 inhibits DNA synthesis via inducement of S‐phase arrest and replication‐dependent histone H2AX phosphorylation; resulting in DNA double‐strand breaks and ultimately cytotoxicity .…”
Section: Exogenous Ligandsmentioning
confidence: 99%
“…Elucidation of substrate specificity between CYP1A1, CYP1A2 and CYP1B1 has been a matter of concern, which is evident from the numerous studies conducted in this regard Nandekar et al, 2013;Pragyan et al, 2014;Tumbi et al, 2014). Recently, the comparative protein structure analysis of the three isoforms of CYP1 family of enzymes was published that focused on sequence alignment (sequence differences), root mean square deviation (RMSD) analysis and B-factor analysis to give a better understanding of the macromolecular features involved in substrate specificity and to understand the interplay between protein dynamics and functions, which have important implications on rational design of anticancer drugs .…”
Section: Introductionmentioning
confidence: 99%
“…Basic mechanistic studies were carried out, including cationic porphyrin-anthraquinone hybrids binding to DNA duplexes (Arba and Tjahjono, 2015 ) and G-quadruplexes (Arba et al, 2016 ), as well as ligands binding to riboswitches upon mutation (Hu et al, 2017 ). The interactions of reactive metabolites of anticancer compounds with DNA were also analyzed (Tumbi et al, 2014 ). In the binding of ligands to riboswitches, Hu et al analyzed the relative binding free energies for a guanine riboswitch (GR) and a GUA complex relative to three complexes: 6GU (3.4 kcal/mol), 2BP (5.48 kcal/mol), and XAN (6.19 kcal/mol).…”
Section: Applications Of Mmpbsamentioning
confidence: 99%